Assembling India's constitution : a new democratic history / Rohit De, Yale University, Ornit Shani, University of Haifa. - De, Rohit; Shani, Ornit (Cambridge University Press, 2025)
In this paradigm-shifting history, two leading historians of India re-examine the making of the Indian constitution from the perspective of the country's people. In a departure from dominant approaches that foreground the framing of the text within the Constituent Assembly, Ornit Shani and Rohit De instead demonstrate how it was shaped by diverse publics across India and beyond. They reveal multiple, parallel constitution-making processes underway across the subcontinent, highlighting how individuals and groups transformed constitutionalism into a medium of struggle and a tool for transformation. De and Shani argue that the deep sense of ownership the public assumed over the constitution became pivotal to the formation, legitimacy and endurance of India's democracy against arduous challenges and many odds. In highlighting the Indian case as a model for thinking through constitution making in plural societies, this is a vital contribution to constitutional and democratic history.